2018
DOI: 10.3390/diseases6010012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Chronic Renal Disease

Abstract: Background: The influence of metabolic syndrome (MetS) on kidneys is related to many complications. We aimed to assess the association between MetS and chronic renal disease defined by a poor estimated glomerular filtration rate (eGFR) and/or the presence of microalbuminuria/macroalbuminuria. Methods: 149 patients (77 males/72 females) were enrolled in the study. Chronic renal disease was defined according to KDIGO 2012 criteria based on eGFR category and classified albuminuria. MetS was studied as a dichotomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…Microalbuminuria is considered a traditional risk marker for the diagnosis and prognosis of declining renal function. Some studies demonstrated an association between insulin resistance and microalbuminuria, and MetS may contribute to the manifestation of albuminuria in patients with diabetes mellitus [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Microalbuminuria is considered a traditional risk marker for the diagnosis and prognosis of declining renal function. Some studies demonstrated an association between insulin resistance and microalbuminuria, and MetS may contribute to the manifestation of albuminuria in patients with diabetes mellitus [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…CKD is associated with metabolic syndrome (MetS), a cluster of metabolic disorders, including hypertension, hyperlipidemia, hyperglycemia, and obesity [3]. MetS contributes to the appearance of albuminuria, the first sign of kidney disease in patients with diabetes [4][5][6]. Moreover, accumulating studies report that obesity is an independent risk factor of CKD [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…CKD, regardless of the causes, and RCC share many risk factors, including age, gender, smoking, hypertension and diabetes mellitus, and these are also related to MetS components. [27] In a large cohort study with nearly 1,200, 000 adults with eGFR< 30 ml/min/1.73 m 2 and a two-fold risk of RCC compared to those with 60-89ml/min/1.73 m, 28 CKD itself was reported to be an independent risk factor for RCC. In order to clarify the effects of MetS and simplify the study design, we controlled for age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Even the MetS-related abnormalities such as hypertension and diabetes mellitus are shown to increase the risk of CKD after nephrectomy. [27] Therefore, MS may re ect a more comprehensive presentation of individuals with CKD risk than each individual component of MS. When Kriegmair et al 12 evaluated the impact of MetS and each of the single components of MetS on outcomes of patients with RCC, the results of Kaplan-Meier and log-rank analysis revealed that MetS was signi cantly associated with a shorter PFS (p=0.018), whereas no signi cant differences were found in the effects of diabetes mellitus, BMI, hypertension and hypertriglyceridemia on the outcomes.…”
Section: Discussionmentioning
confidence: 99%